(Un-)related variety and employment growth at the sub-regional level - Matthias Firgo; Peter Mayerhofer (Austrian Institute of Economic Research (WIFO), 2016)
Empirical results on the link between growth and diversity in (un)related industries proved to be highly dependent on the specific regional and temporal context. Making use of highly disaggregated employment data at the sub-regional level, we find that higher employment growth in Austria is mainly linked to unrelated variety. However, in-depth analyses by sectors and regional regimes illustrate substantial heterogeneity in the results, mainly driven by the service sector and by a large number of relatively small regions. Thus, our results argue against structural policy conclusions based on assessments across all economic sectors or different types of regions.
Keywords: D62; J24; O33; R11; R58; 330; related variety; specialization; knowledge spillovers; employment growth; structural policy